Motor fluctuations due to interaction between dietary protein and levodopa in Parkinson's disease. Issue 1 (December 2016) - Virmani, Tuhin; Tazan, Sirinan; Mazzoni, Pietro; Ford, Blair; Greene, Paul
Abstract Background The modulation of levodopa transport across the blood brain barrier by large neutral amino acids is well documented. Protein limitation and protein redistribution diets may improve motor fluctuations in patients with Parkinson's disease but the pharmacokinetics and pharmacodynamics of levodopa and amino acids are highly variable. Methods Clinical records of 1037 Parkinson's disease patients were analyzed to determine the proportion of patients with motor fluctuations related to protein interaction with levodopa. Motor fluctuations due to protein interaction with levodopa were defined as dietary protein being associated with (i) longer time to levodopa effectiveness, (ii) reduced benefit or duration of benefit, (iii) dose failures or (iv) earlier wearing off from a previously effective dose. Dose failures, sudden, painful or behavioral wearing-off periods, gait freezing, nausea, hallucinations, orthostasis, and dyskinesias were taken as markers of motor fluctuations, disease severity, and levodopa side effects potentially influenced by protein. Results 5.9 % of Parkinson's disease patients on levodopa, and 12.4 % with motor fluctuations on levodopa correlated their fluctuations with the relative timing of levodopa and protein intake. These patients were younger at disease onset, had worse motor fluctuations and had a higher incidence of family members with Parkinson's disease. Early wearing off or decreased dose efficacy were most commonly associated with protein interaction. 60 % of patients who modified their diets had weight loss. Conclusions This study suggests that clinically significant protein interaction with levodopa may occur mostly in a subset of Parkinson's disease patients with earlier disease onset and those with familial disease.